Kebijakan Pengendalian Deforestasi dan Restorasi Ekosistem - Farah Fadilla Putri,; Eli Apud Saepudin,; Widya Nurfitriani,; Diah Karmila,; Salsabila, (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study evaluates the effectiveness of deforestation reduction strategies and ecosystem restoration programs in Indonesia from 2015 to 2024. Using a combination of spatial analysis, a comprehensive literature review, and intensive stakeholder interviews, the study found a 21.3% reduction in deforestation, but substantial barriers to policy implementation. Based on the results obtained, the success of ecosystem restoration initiatives is largely determined by the involvement of local communities, certainty of land rights, and harmonization between national regulations and implementation at the local level. The research revealed a disparity between policy formulation and practical actualization, due to weak collaboration between sectors, limited technical capabilities, and lack of adequate financial support. The study concludes that a comprehensive strategy that combines law enforcement, community empowerment and sustainable economic incentive schemes is a critical success factor in controlling deforestation and restoring ecosystems. An important contribution of this research is to provide a more flexible and context-appropriate policy framework to address deforestation issues while promoting the rehabilitation of degraded forest areas.